Examining the relationship between information processing strategies and disordered eating behaviour - Ralph-Nearman, Christina (2018)
Many cognitive theories point to key factors underlying the development and maintenance of eating disorders, such as: unhealthy food-related cognitive biases, negative body attitude, and perfectionism. The present research utilised eye-tracking during reading as a novel implicit measure of how these factors may relate to eating disorder tendencies in females and males, followed by the development of two new male body dissatisfaction scales. In four experiments female and male (N = 360) participants’ eye movements were monitored while they read third- and second-person perspective texts in which the characters’ emotional responses to food-, body image-, and perfectionism-related scenarios were described. Overall, results from these studies suggest that on-line processing of characters’ emotional responses to perfectionism-, and to a lesser extent, body image-related information is predictive of participants’ disordered eating tendencies, thus supporting theories in which these two underlying factors are key to developing and maintaining eating disorders. Interestingly, the on-line processing of characters’ emotional responses to food-related scenarios did not predict eating disorder tendencies, as participants read food-related scenarios similarly, regardless of having a higher eating disorder level. In Chapter V, two new male body dissatisfaction scales: The Male Body Scale (MBS; consisting of emaciated to obese figures) and the Male Fit Body Scale (MFBS; consisting of emaciated to muscular figures) were developed, tested, and re-tested. Male participants (N = 103) rated which of nine body figures on each scale most represented their current- and ideal- body figure, followed by the Drive for Muscularity Scale (DMS), the Eating Disorder Examination Questionnaire (EDE-Q 6.0), and the calculation of their actual body mass index (BMI), fat-, and muscularity-percentage. This was followed by a re-test and manipulation check two to six weeks later. Results found both new scales were consistently valid and reliable between test and re-test, and importantly, each scale was sensitive to different types of body dissatisfaction within males. Specifically, the MBS revealed that males’ desire for the thin-ideal significantly corresponded to higher eating disorder tendencies as shown by EDE-Q 6.0 scores, whilst the MFBS revealed much higher body dissatisfaction toward the larger, muscularity-ideal, predicting higher drive for muscularity as shown by DMS scores. Altogether, the present research findings provide novel insights into cognitive processes underlying disordered eating behaviour, demonstrate the utility of eye-tracking as a more natural implicit measure, provide tools to assess and predict eating disorder tendencies in females and males, and inform eating disorder related research.